International Indigenous Business and Trade and the Role of Culture: A Comparison between Aotearoa Māori and Alaska Native Enterprises - Mika, Jason Paul; Ross, Betty M.E. (Journal of Aboriginal Economic Development, 2019)
Indigenous enterprises are increasingly engaging in international business and trade, mainly in agriculture, forestry, fishing, and tourism, to grow Indigenous economies. The experiences of the Indigenous peoples of Aotearoa New Zealand (the Māori) and of Alaska provide a context and case through which to explore cross-cultural exchanges in business. In this conceptual paper, we review literature on the role of culture in international business and trade, focusing on indigeneity in international Indigenous business. We find that when commonality and mutual respect are established in cross-cultural exchanges in business, there is said to be cultural congruity. When material cultural differences inhibit cross-cultural business, there is cultural discordance. Specific examples are used to show how Indigenous firms in Aotearoa New Zealand and in Alaska compare. This paper provides scope for other Indigenous peoples to explore how their cultures influence firm-level performance and international trade.